2023
DOI: 10.1021/acs.jafc.2c08919
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Phthalate Esters in Tea Plants Growing Different Geographical Environments and an Attempt on Their Risk Assessment

Abstract: The phthalate esters (PAEs) have become ubiquitous pollutants. In the present work, we investigated their pollution on teas. Dimethyl phthalate (DMP), diethyl phthalate (DEP), diisobutyl phthalate (DiBP), di-n-butyl phthalate (DBP), and di-(2ethyl) hexyl phthalate (DEHP) were detected in all fresh tea leaves with DBP being the major congener of PAEs in teas followed by DiBP and DEHP. Seasonal variation, spatial distribution difference, correlationship of environmental factors, and potential health risks of PAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(123 reference statements)
2
0
0
Order By: Relevance
“…Therefore, it is inferred that aside from the root absorption, plasticizers in stevia leaves can be absorbed into the plant body through the leaves. This conclusion is consistent with the results obtained by Professor Wang et al that indicated a positive correlation between the plasticizers in tea leaves and the air quality [12]. The use of plastic mulch during the cultivation of stevia provides an environment in which the plasticizers in the mulch come into contact with stevia and are absorbed by the stevia leaves through dust or air during the growth period.…”
Section: Distribution Of Phthalates In Stevioside Plant Tissuessupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it is inferred that aside from the root absorption, plasticizers in stevia leaves can be absorbed into the plant body through the leaves. This conclusion is consistent with the results obtained by Professor Wang et al that indicated a positive correlation between the plasticizers in tea leaves and the air quality [12]. The use of plastic mulch during the cultivation of stevia provides an environment in which the plasticizers in the mulch come into contact with stevia and are absorbed by the stevia leaves through dust or air during the growth period.…”
Section: Distribution Of Phthalates In Stevioside Plant Tissuessupporting
confidence: 92%
“…The detection results indicate that phthalate contamination was present in all the samples tested, and the influence of regional factors at the provincial level on the content of plasticizers in stevia leaves was not significant. A similar conclusion was reached by Wang et al in the research on the spatiotemporal dynamics of phthalates in tea plants growing in different geographical environments [12].…”
Section: Distribution Of Phthalates In Stevioside Plant Tissuessupporting
confidence: 83%